A perspectiva de cuidadores primários acerca do diagnóstico da Síndrome de Down e o processo de adaptação da família nos primeiros anos de vida da criança. - Debora Lara Couto (2017)
The Down syndrome (DS) diagnosisinformation causes changes in the dynamics of family functioning, since it is an unexpected event and unwanted by the parents. This study aimed in generalto analyze the perspectives of primary caregivers about the diagnosis of Down Syndromeand the process of families adaptation with children up three years of age. It is a qualitative, exploratory-type study guided by McCubbin and McCubbin's (2003) theoretical framework of the Resilience Model, stress, adjustment and family adaptation. Twenty primary caregivers of children with SD one andthree years old participated. Data collection was performed through a semi-structured interview, genogram and ecomapa construction and field diary notes, in the places chosen by the participants. The data analysis was performed by the Direct Content Analysis, using the software MAXQDA ©, version 12.2.0. An individual analysis of the families was carried out, and later four categories of analysis were constructed, guided by the model used as theoretical reference: 1) Information on the diagnosis of Down syndrome to the family; 2) Family vulnerability and demands inherent to the stressor event; 3) Family appreciation about Down syndrome; 4) Family confrontation in relation to the stressor event. It was possible to understand the various components that are part of the information context of the diagnosis of SD and that can interfere in the family's appreciation of it, and consequently in the adaptation process. Situations have been identified that have made the family system more vulnerable, as well as the demands and challenges that arise from the diagnosis, which generate the need for reorganization in family functioning. Caregivers refer to negative feelings and experiences regarding information on the diagnosis of DS, however, overtime, they express a more positive appreciation about the situation of having a child with DS. In relation to resources used and coping strategies of the family, the support of the family, support of health professionals, support of groups of families and support of other mothers of children with DS, spirituality and religiosity, health follow-ups, and Family coping. The elements that constitute the process of adaptation according to the theoretical reference, as well as their interrelation, were visualized and understood in the families studied. The study contributes to the identification of the skills and abilities needed by health professionals who deal with the context of the diagnosis of DS, and allows them to identify the fragilities and potentialities of the family in order to favor the process of family adaptation. In addition, it broadens the knowledge of the general population about the diagnosis of Down syndrome and the process of adaptation, and contributes to the appreciation and adaptation of other families who are experiencing this moment. We emphasize the importance of new studies on the subject, especially in other age groups, in order to allow the understanding of the family system in other stages of life of the individual with DS.